In blood and ashes: curse tablets and binding spells in Ancient Greece - Lamont, Jessica L. (Oxford University Press, 2023)
In Blood and Ashes provides the first historical study of the development and dissemination of ritualized curse practice in the ancient Greek world (c. 750-250 BCE). Filled with new material and insights, the volume offers a fresh perspective on ancient Greek social history and religion, highlighting the importance of ritual in negotiating life's uncertainties.